IMPROVING CREDIT PROCESSES IN COMMERCIAL BANKS THROUGH THE IMPLEMENTATION OF DIGITAL TECHNOLOGIES: A COMPREHENSIVE ANALYSIS - Azimov Otabek Ma’mirjon o’g’li (Ecominds Press, 2025)
This comprehensive research examines the transformative impact of digital technologies on credit processes in Uzbekistan's commercial banking sector. The study provides an in-depth analysis of how digitalization is reshaping traditional banking operations, with a particular focus on credit processes. Through extensive quantitative and qualitative research, including surveys of banking professionals, comparative analysis of international best practices, and econometric modeling, this paper evaluates the current state of digital implementation in Uzbekistan's banking system and identifies key opportunities for advancement. The research demonstrates that digital technologies can reduce credit processing time by up to 85%, decrease operational costs by 30-50%, and significantly enhance risk assessment accuracy. The study reveals that while Uzbekistan's major banks have initiated digital transformation efforts, achieving an average digitalization level of 45%, they continue to face significant challenges in infrastructure development, data quality, staff competencies, financial resources, and cybersecurity. Based on comprehensive analysis, the paper proposes a strategic framework for accelerating digital transformation in credit processes that includes seven key directions: developing integrated digital credit platforms, implementing artificial intelligence for credit scoring, expanding open banking systems, utilizing blockchain for smart contracts, enhancing biometric identification, improving staff digital competencies, and strengthening cybersecurity measures. This research contributes to the theoretical understanding of banking digitalization and offers practical guidance for banking institutions and regulatory authorities in Uzbekistan and other developing economies.
Keywords: banking digitalization, credit process optimization, artificial intelligence in banking, digital credit scoring, automated decision-making, fintech innovation, Uzbekistan banking sector, digital transformation strategy, online banking services, banking cybersecurity.